Responden Peserta Didik dan Guru terhadap Kemampuan Berpikir Kritis SMA Negeri 3 Pekanbaru - Fira Herlini; Sepita Ferazona; Nurkhairo Hidayati (Concept: Journal of Social Humanities and Education, 2024)
This study aims to analyze teachers' and students' responses to critical thinking skills in biology learning at SMA Negeri 3 Pekanbaru. The research employed a descriptive qualitative method using observation, interviews, and documentation. The subjects were 11th-grade students and biology teachers. The results indicate that the evaluation process conducted by teachers was inconsistent. Essay-based evaluations were deemed effective in measuring critical thinking skills, although not always based on specific indicators. Most students assessed critical thinking questions as moderately difficult, with their evaluation results categorized as high. However, a gap in students' understanding was identified, requiring further attention. This study recommends the systematic use of critical thinking indicators to better support the development of students' critical thinking skills.